On the numerical solution of a rising sphere in a Newtonian fluid with temperature-dependent viscosity - Zambrano, Marcos (2019)
In this work, we present some numerical results about the problem of a rising hot solid sphere immersed in a Newtonian fluid which viscosity depends on the temperature. The model formulated to solve the problem considers two dimensionless parameters: The Peclet number, Pe and a parameter related with the viscosity, e. Small and large variations on e lead to interesting results segregated into two regimes which exhibit an asymptotic structure.To carry out the computations to solve the proposed model, the element finite method was used along with a non-slip boundary condition for the contact surface between the sphere and the fluid and the results obtained were compared to those shown recently in papers related wherein contact surface has a slip-boundary condition prescribed.